Monitoring the agri-food system in Myanmar: Agricultural input retailers – July 2022 survey round - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
To understand the effects of political instability, COVID-19, and other shocks on Myanmar’s agricultural input sector, a phone survey of 252 input retailers throughout the country was conducted in July 2022.